2023
DOI: 10.1371/journal.pone.0292946
|View full text |Cite
|
Sign up to set email alerts
|

The indole motif is essential for the antitrypanosomal activity of N5-substituted paullones

Irina Ihnatenko,
Marco J. Müller,
Oliver C. F. Orban
et al.

Abstract: Severe infections with potentially fatal outcomes are caused by parasites from the genera Trypanosoma and Leishmania (class Kinetoplastea). The diseases affect people of remote areas in the tropics and subtropics with limited access to adequate health care. Besides insufficient diagnostics, treatment options are limited, with tenuous developments in recent years. Therefore, new antitrypanosomal antiinfectives are required to fight these maladies. In the presented approach, new compounds were developed and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Several of the new derivatives showed good inhibitory properties behaving as uncompetitive enzyme inhibitors and resulted in improved potency and selectivity against L. braziliensis and L. infantum [148]. Recently, it has been reported that the indole moiety of N 5 -substituted paullones is essential for keeping the TryS-inhibitory and antitrypanosomal activity of this type of compound [149].…”
Section: Substrate or Transition State Analogsmentioning
confidence: 99%

Targeting Trypanothione Metabolism in Trypanosomatids

González-Montero,
Andrés-Rodríguez,
García-Fernández
et al. 2024
Molecules
“…Several of the new derivatives showed good inhibitory properties behaving as uncompetitive enzyme inhibitors and resulted in improved potency and selectivity against L. braziliensis and L. infantum [148]. Recently, it has been reported that the indole moiety of N 5 -substituted paullones is essential for keeping the TryS-inhibitory and antitrypanosomal activity of this type of compound [149].…”
Section: Substrate or Transition State Analogsmentioning
confidence: 99%

Targeting Trypanothione Metabolism in Trypanosomatids

González-Montero,
Andrés-Rodríguez,
García-Fernández
et al. 2024
Molecules